Manajemen Kesiswaan Pada Madrasah Tsanawiyah Al Iman Bulus Gebang Purworejo Tahun Ajaran 2019/2020 - Musolin, Muhlil (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2020)
Student management is a very important thing applied to educational institutions. Student management is the entire process of planned and deliberately pursued activities and continuous development of all students in the relevant educational institutions in order to be able to follow the teaching and learning process effectively and efficiently. This study aims to determine the implementation of student management in MTs Al Iman Bulus Gebang Purworejo. This study uses a naturalistic qualitative approach. Sources of data were obtained through interviews with the administrative field of MTs Al Iman Bulus Gebang Purworejo. The results showed the implementation of student management in Madrasah Tsanawiyah (MTs) Al Iman Bulus Gebang Purworejo, which was in planning including the implementation of new student admission programs by forming committees, analyzing the capacity of new students, and the selection process of new students. The implementation of student management is manifested by the orientation of new students, regulating the attendance and absence of students, grouping students, managing students who are mutated and dropped out. Supervision is realized by the existence of a code of ethics, court, punishment and discipline of school students. Evaluation is held by midterm and end of semester exams as well as consideration in improving students' classes.